Identification Of Determining Factors Of Community Decisions In Selecting Sharia And Conventional Banks - Nofinawati Nofinawati; Jumi Atika (Institut Agama Islam Negeri Padngsidimpuan, 2020)
Abstract The people of North Sumatra Province, especially the South Tapanuli region which are diverse in terms of their religion, there are Muslims, Christians and other religions. However, religious factors or perceptions that are only based on religious reasons do not necessarily affect people's behavior towards decisions about using this type of banking service. Seeing the many factors that determine customer decisions in using banking services. The type of research is a quantitative field research. The marketing mix variable partially cannot be used as a determining factor for community decisions in choosing Sharia and conventional banks in North Sumatra Province. While motivation and perception variables can be partially used as a determining factor for community decisions in choosing Sharia and Conventional Then, the motivation, perception and marketing mix variables can simultaneously be used as a determining factor for community decisions in choosing Sharia and Conventional Banks in North Sumatra Province. Abstrack Masyarakat Provinsi Sumatera Utara, khususnya wilayah Tapanuli Selatan memiliki agama yang beragam, ada Muslim, Kristen dan agama lain. Namun, faktor atau persepsi keagamaan yang hanya didasarkan pada alasan keagamaan tidak serta merta mempengaruhi perilaku masyarakat terhadap keputusan tentang penggunaan jenis layanan perbankan. Melihat banyak faktor yang menentukan keputusan pelanggan dalam menggunakan layanan perbankan. Jenis penelitian adalah penelitian kuantitatif. Variabel bauran pemasaran secara parsial tidak dapat digunakan sebagai faktor penentu bagi keputusan masyarakat dalam memilih Syariah dan bank konvensional di Provinsi Sumatera Utara. Sementara variabel motivasi dan persepsi sebagian dapat digunakan sebagai faktor penentu untuk keputusan masyarakat dalam memilih Syariah dan Konvensional Kemudian, variabel motivasi, persepsi dan bauran pemasaran secara bersamaan dapat digunakan sebagai faktor penentu untuk keputusan.